The effectiveness of surgical wound dressing by nurses for patients undergoing elective surgery in Hospital Universiti Sains Malaysia Kelantan. - Suntarajoo, Purani A/P (2003)
Introduction: The incidence of surgical site infection is 23.3% in Hospital Universiti Sains Malaysia in the year 2000. The causeS of surgical site infections include poor care during preoperative, intraoperative and postoperative period During postoperative period, the surgical wound dressing by nurses play a significant role in the occurrence of surgical site infection. Objective: To reduce the rate of surgical site infection by identifying the risk factor for surgical site infection and the effectiveness of surgical wound dressing Methodology: Data collection was done using pro forma through follow up of patients. Data were collected· on the 3rd and 7th postoperative day for each sample. The pro forma composed of two section. The first section contains demographic data and another section consist of investigation data. In the investigation section, the data was divided into three categories which were related to the surgery undergone , dressing done by nurses and parameter used to identify surgical wound infection. Wound culture was taken on day 3 and day?. Results: Six out of 15 patients underwent elective surgery developed surgical site infection attributable to poor preoperative and intraoperative care. Four out of the 15 patients developed surgical site infection attributable to poor wound dressing. Conclusion: The risk factors for surgical site infection include, the type of surgery (TAHBSO}, the duration of surgery (more then 1 hour) and the dressing by op-site spray. The preoperative prophylaxis and the. frequency of-dressing did not influence· the incidence of surgical site infection. Due to time constrain~ only a small number of sample could be induded in this study. A study including a large number of sample would be recommended to support the findings of this study.